Preparation method of titanium dioxide-calcium carbonate composite photocatalytic material
Porous titanium dioxide structures were prepared through microarc oxidation technology and reacted with calcium carbonate to form a composite structure, which solved the problems of narrow light absorption range and low photocatalytic efficiency of titanium dioxide, and achieved a significant improvement in photocatalytic efficiency and response range.
Patent Information
- Application Number
- CN202411583338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
As a wide-bandgap semiconductor, titanium dioxide has a narrow light absorption range, mainly in the ultraviolet light region, and has problems such as short electron-hole pair lifetime, low photocatalytic quantum utilization, easy agglomeration of particles and difficulty in recycling and separation.
Microarc oxidation technology is used to prepare porous titanium dioxide structures, and a titanium dioxide-calcium carbonate composite structure is formed by centrifugal oscillation reaction with calcium carbonate to expand its photoresponse range and improve photocatalytic efficiency.
It significantly improves the photocatalytic efficiency, expands the light response range, enhances its absorption and utilization ability of visible light, extends service life, and reduces waste emissions and energy consumption.
Smart Images

Figure CN119456002A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of semiconductor materials, in particular to a method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material. Background Art
[0002] When titanium dioxide is irradiated by photons with energy greater than or equal to the band gap, the valence band electrons are excited to the conduction band and become photogenerated electrons. At this time, the valence band generates positively charged photogenerated holes, which can degrade organic pollutants into low-molecular harmless substances. Therefore, titanium dioxide has very important research value in water pollution control and other aspects. However, titanium dioxide is a wide bandgap semiconductor with a band gap of 3.2eV, and it will only be excited under ultraviolet light with a wavelength less than 350nm. In addition, titanium dioxide also has problems such as short electron-hole pair lifetime, low photocatalytic quantum utilization, easy agglomeration of particles, and difficulty in recycling and separation. Summary of the invention
[0003] To solve the above problems, the present invention provides a method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material. The titanium dioxide-calcium carbonate composite structure combines the characteristics of the two materials. The preparation method of the present invention reduces waste emissions and energy consumption, and is more in line with the requirements of environmental protection and energy saving. At the same time, the composite structure can effectively degrade organic pollutants in photocatalytic applications, providing strong support for environmental protection.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material,
[0005] The method comprises the steps of: grinding and cleaning the surface of the pure titanium sample to remove the oil stains and oxide layer on the surface, and drying the sample for standby use;
[0006] Step 2: using the pure titanium sample treated in step 1 as the anode of the micro-arc oxidation reaction and the stainless steel electrolytic cell as the cathode, adding electrolyte into the stainless steel electrolytic cell to perform micro-arc oxidation reaction and prepare a porous titanium dioxide structure;
[0007] Step 3: Clean the porous titanium dioxide structure, dry it and set it aside;
[0008] Step 4: The micro-arc oxidation sample treated in step 3 is placed in a mixed reaction solution of deionized water, Na2CO3 and Ca(NO3)2 and centrifuged for 10-20 minutes. After the reaction is completed, it is cleaned and dried to obtain a titanium dioxide-calcium carbonate composite structure.
[0009] Furthermore, in step 1, a pure titanium sample with a diameter of 10-20 mm and a thickness of 0.5-1 mm is polished step by step using 240#, 800#, and 1500# sandpapers, and then ultrasonically cleaned with ultrapure water for 5-10 minutes. After cleaning, it is dried at 80° C. in a blast drying oven for 6-12 hours and then used for later use.
[0010] Furthermore, in step 2, the electrolyte adopts a phosphate system electrolyte or a silicate system electrolyte.
[0011] Furthermore, the phosphate system electrolyte is prepared by mixing disodium hydrogen phosphate, sodium hydroxide, and disodium ethylenediaminetetraacetate in a ratio of 5-9:1-3:4-7.
[0012] Furthermore, the silicate system electrolyte is prepared by mixing calcium chloride, sodium silicate and disodium ethylenediaminetetraacetate in a ratio of 1:1:1 to 4.
[0013] Furthermore, in step 2, the micro-arc oxidation reaction adopts a constant voltage mode, with a voltage of 250-400 V, a frequency of 20-60 Hz, a duty cycle of 20%-60%, and a reaction time of 3-15 min.
[0014] Further, in step 3, the porous titanium dioxide structure is ultrasonicated with ultrapure water for 3 to 6 minutes, the ultrapure water is replaced and ultrasonicated for another 3 to 6 minutes, and this is repeated 3 to 5 times to clean the surface. After drying at 80° C. in a forced air drying oven for 6 to 12 hours, the sample is placed in a drying dish for later use.
[0015] Further, in step 4, the micro-arc oxidation sample treated in step 3 is placed in a centrifuge tube, and 30 ml of deionized water, a Ca(NO3)2 and Na2CO3 solution with a molar ratio of 1:2 are added to the centrifuge tube, and centrifugal oscillation is performed for 10-20 minutes.
[0016] The beneficial effects of the present invention are:
[0017] Improve photocatalytic efficiency: By combining the characteristics of titanium dioxide and calcium carbonate, the titanium dioxide-calcium carbonate composite structure significantly improves the photocatalytic efficiency. Compared with traditional titanium dioxide photocatalysts, the composite structure shows better performance in photocatalytic hydrogen production and degradation of organic pollutants.
[0018] Expanding the light response range: Titanium dioxide is a wide-bandgap semiconductor with a narrow light absorption range, mainly in the ultraviolet region. The introduction of calcium carbonate can effectively expand the light response range of titanium dioxide, enhance its ability to absorb and utilize visible light, and thus improve the utilization rate of light energy.
[0019] Enhanced photocatalytic durability: The titanium dioxide-calcium carbonate composite structure exhibits good durability in the photocatalytic reaction. Due to the presence of calcium carbonate, the composite structure can better maintain its photocatalytic activity, extend its service life, and reduce the frequency of catalyst replacement.
[0020] Improved material stability: The titanium dioxide-calcium carbonate composite structure has high chemical stability and thermal stability. During the photocatalytic reaction, the composite structure can resist the erosion of corrosive media such as acids and alkalis, maintaining its structural integrity and catalytic activity.
[0021] Simplified preparation process: The preparation method of the present invention adopts micro-arc oxidation technology to generate a porous titanium dioxide structure in situ on the surface of the titanium substrate, and prepares a titanium dioxide-calcium carbonate composite structure through a simple centrifugal oscillation reaction. The process equipment is simple, easy to operate, and suitable for large-scale industrial production.
[0022] Environmental protection and energy saving: Compared with the traditional titanium dioxide preparation process, the preparation method of the present invention reduces waste emissions and energy consumption, and is more in line with the requirements of environmental protection and energy saving. At the same time, the composite structure can effectively degrade organic pollutants in photocatalytic applications, providing strong support for environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the titanium dioxide-calcium carbonate composite structure obtained in Example 1 observed by a scanning electron microscope (SEM).
[0024] Figure 2 The degradation of methylene blue by each titanium dioxide-calcium carbonate sample. DETAILED DESCRIPTION
[0025] The present application provides a method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material.
[0026] The method comprises the steps of: grinding and cleaning the surface of the pure titanium sample to remove the oil stains and oxide layer on the surface, and drying the sample for standby use;
[0027] Step 2: using the pure titanium sample treated in step 1 as the anode of the micro-arc oxidation reaction and the stainless steel electrolytic cell as the cathode, adding electrolyte into the stainless steel electrolytic cell to perform micro-arc oxidation reaction and prepare a porous titanium dioxide structure;
[0028] Step 3: Clean the porous titanium dioxide structure, dry it and set it aside;
[0029] Step 4: The micro-arc oxidation sample treated in step 3 is placed in a mixed reaction solution of deionized water, Na2CO3 and Ca(NO3)2 and centrifuged for 10-20 minutes. After the reaction is completed, it is cleaned and dried to obtain a titanium dioxide-calcium carbonate composite structure.
[0030] Furthermore, in step 1, a pure titanium sample with a diameter of 10-20 mm and a thickness of 0.5-1 mm is polished step by step using 240#, 800#, and 1500# sandpapers, and then ultrasonically cleaned with ultrapure water for 5-10 minutes. After cleaning, it is dried at 80° C. in a blast drying oven for 6-12 hours and then used for later use.
[0031] Furthermore, in step 2, the electrolyte adopts a phosphate system electrolyte or a silicate system electrolyte.
[0032] Furthermore, the phosphate system electrolyte is prepared by mixing disodium hydrogen phosphate, sodium hydroxide, and disodium ethylenediaminetetraacetate in a ratio of 5-9:1-3:4-7.
[0033] Furthermore, the silicate system electrolyte is prepared by mixing calcium chloride, sodium silicate and disodium ethylenediaminetetraacetate in a ratio of 1:1:1 to 4.
[0034] Furthermore, in step 2, the micro-arc oxidation reaction adopts a constant voltage mode, with a voltage of 250-400V, a frequency of 20-60Hz, a duty cycle of 20%-60%, and a reaction time of 3-15min.
[0035] Further, in step 3, the porous titanium dioxide structure is ultrasonicated with ultrapure water for 3 to 6 minutes, the ultrapure water is replaced and ultrasonicated for another 3 to 6 minutes, and this is repeated 3 to 5 times to clean the surface. After drying at 80° C. in a forced air drying oven for 6 to 12 hours, the sample is placed in a drying dish for later use.
[0036] Further, in step 4, the micro-arc oxidation sample treated in step 3 is placed in a centrifuge tube, and 30 ml of deionized water and a Ca(NO3)2 and Na2CO3 solution with a molar ratio of 1:2 are added to the centrifuge tube, and centrifuged for 10-20 minutes.
[0037] The following is the specific preparation process:
[0038] Comparative group: Precise preparation steps of titanium dioxide samples:
[0039] Surface pretreatment: Use a pure titanium sample with a diameter of 15 mm and a thickness of 0.75 mm. Use 240#, 800#, and 1500# sandpaper to polish the surface step by step until it is smooth, so as to completely remove the oil and oxide layer on the surface.
[0040] Ultrasonic cleaning: Place the polished pure titanium sample in ultrapure water and use an ultrasonic cleaner to clean it for 8 minutes to ensure that surface impurities are completely removed.
[0041] Drying: Place the cleaned pure titanium sample in a forced air drying oven and dry it at 80°C for 10 hours to ensure that the inside and surface of the sample are completely dry.
[0042] Micro-arc oxidation reaction: The pretreated pure titanium sample is used as the anode and the stainless steel electrolytic cell is used as the cathode. A phosphate system electrolyte (disodium hydrogen phosphate, sodium hydroxide, and disodium ethylenediaminetetraacetic acid are mixed and modulated in a ratio of 7:2:5.5) is added to the electrolytic cell. When performing the micro-arc oxidation reaction, a constant voltage mode is adopted, the voltage is set to 300V, the frequency is set to 40Hz, the duty cycle is set to 40%, and the reaction time is set to 10 minutes. After the reaction is completed, a porous titanium dioxide structure is obtained.
[0043] Cleaning and drying: The porous titanium dioxide structure was ultrasonically cleaned with ultrapure water for 4 minutes, and the ultrapure water was replaced and ultrasonically cleaned for another 4 minutes, and the process was repeated once, for a total of three cleanings. The structure was then dried in a blast drying oven at 80°C for 10 hours to obtain a titanium dioxide sample.
[0044] Embodiment 1:
[0045] The above precisely prepared titanium dioxide sample is carefully placed in a 50mL centrifuge tube. Subsequently, 30ml of deionized water is added to the centrifuge tube as a reaction medium. Next, the first group of reactants, namely 5ml of 0.05M Ca(NO3)2 solution and 10ml of 0.1M Na2CO3 solution (ensuring that the molar ratio of Ca(NO3)2 and Na2CO3 is 1:2) are added to the reaction system. After the centrifuge tube is sealed, it is placed on an oscillator for centrifugal oscillation for 10 minutes. After the oscillation is completed, the titanium dioxide sample is removed from the centrifuge tube and thoroughly rinsed with deionized water to remove excess reactants and impurities attached to the surface of the sample. After rinsing, the sample is placed in a blast drying oven for drying. After drying, the sample is placed in a drying dish for storage for subsequent testing and analysis. The sample is named titanium dioxide-calcium carbonate-1 sample.
[0046] Embodiment 2:
[0047] Similar to Example 1, titanium dioxide sample is placed in 50mL centrifuge tube, and 30ml of deionized water is added.But in this embodiment, what is added in reaction system is second group of reactants, i.e. 10ml of 0.1M Ca (NO ) 2 solution and 20ml of 0.2M Na 2 CO 3 solution (equally ensuring Ca (NO ) 2 and Na 2 CO 3 mol ratio is 1: 2).After centrifugal vibration for 10 minutes, take out sample and rinse with deionized water.After drying, sample is placed in drying dish and preserved, and this sample is named as titanium dioxide-calcium carbonate-2 sample.In addition, titanium dioxide-calcium carbonate-2 sample prepared by this embodiment can also be observed by scanning electron microscope (SEM), to obtain the information of its microstructure and morphology.
[0048] Embodiment 3:
[0049] In Example 3, the preparation process of the titanium dioxide sample is the same as that of the first two examples. However, in this example, the third group of reactants, i.e., 20 ml of 0.2 M Ca(NO3)2 solution and 40 ml of 0.4 M Na2CO3 solution, are added to the reaction system (also ensuring that the molar ratio of Ca(NO3)2 to Na2CO3 is 1:2). After centrifugal oscillation for 10 minutes, the sample is taken out and rinsed with deionized water. After drying, the sample is placed in a drying dish for storage, and the sample is named titanium dioxide-calcium carbonate-3 sample.
[0050] The following is a detailed discussion of the photocatalytic activity evaluation of the titanium dioxide-calcium carbonate composite structure.
[0051] 1. Experimental Methods
[0052] In order to evaluate the photocatalytic activity of the prepared titanium dioxide-calcium carbonate composite structure, we used the methylene blue degradation experiment. The specific experimental steps are as follows:
[0053] Experimental preparation: Measure 20 ml of 2 mg / L methylene blue solution, and accurately weigh 0.1 g of catalyst powder (titanium dioxide sample and titanium dioxide-calcium carbonate composite structure sample, specifically titanium dioxide sample (titanium dioxide sample prepared in the above-mentioned control group), titanium dioxide-calcium carbonate-1, titanium dioxide-calcium carbonate-2, titanium dioxide-calcium carbonate-3).
[0054] Dark box adsorption: Add the methylene blue solution and catalyst powder into a 100 ml beaker and place it in a dark box. Use a magnetic stirrer to stir for 20 minutes to ensure that the catalyst powder is fully in contact with the methylene blue solution and reaches adsorption equilibrium.
[0055] Photocatalytic degradation: Turn on a 20W fluorescent lamp with a wavelength of 400-700nm, continue magnetic stirring for 1 hour, and conduct a photocatalytic degradation experiment. During this process, the light emitted by the fluorescent lamp will excite the active sites on the catalyst surface, thereby initiating the degradation reaction of methylene blue.
[0056] Sampling analysis: After 1 hour, take 5 ml of the sample from the beaker and centrifuge it to remove the catalyst powder in the solution. Take the supernatant and measure its absorbance at 662 nm using a UV-visible spectrophotometer. Based on the relationship that the concentration of methylene blue is proportional to the absorbance, the absorbance A and A0 before and after degradation can be calculated.
[0057] Degradation rate calculation: The degradation rate of methylene blue was calculated according to the formula “degradation rate (%) = (1-A / A0) × 100%” to evaluate the photocatalytic activity of the catalyst.
[0058] 2. Experimental Results
[0059] Figure 2 The degradation of methylene blue in each group is shown. It can be seen from the figure that compared with pure titanium dioxide samples, the titanium dioxide-calcium carbonate composite structure (titanium dioxide-calcium carbonate-1, titanium dioxide-calcium carbonate-2, titanium dioxide-calcium carbonate-3) has a significantly better photocatalytic effect. Specifically, the degradation rate of the titanium dioxide-calcium carbonate composite structure (titanium dioxide-calcium carbonate-1, titanium dioxide-calcium carbonate-2, titanium dioxide-calcium carbonate-3) is significantly higher than that of the titanium dioxide sample, and can be increased to about 3 times. This shows that the photocatalytic activity of titanium dioxide can be significantly improved by introducing calcium carbonate.
[0060] In addition, Example 1: In this embodiment, 5 ml of 0.05M Ca(NO3)2 solution and 10 ml of 0.1M Na2CO3 solution were added to the reaction system to ensure that the molar ratio of Ca(NO3)2 and Na2CO3 was 1:2. According to the chemical reaction equation Ca(NO3)2+Na2CO3=calcium carbonate↓+2NaNO3, the amount of calcium carbonate generated can be calculated. Since Ca(NO3)2 is the limiting reagent in the reaction (because its molar amount is small), the amount of calcium carbonate generated is equal to the amount of Ca(NO3)2, i.e., 0.0025 mol. Considering the surface area and reaction conditions of the titanium dioxide sample, this part of calcium carbonate may be deposited on the titanium dioxide surface with a certain coverage.
[0061] Example 2: In this example, 10 ml of 0.1 M Ca(NO3)2 solution and 20 ml of 0.2 M Na2CO3 solution were added. Similarly, according to the chemical reaction equation, the amount of calcium carbonate generated was 0.01 mol, which is 4 times that of Example 1. This means that in Example 2, more calcium carbonate will be deposited on the surface of titanium dioxide.
[0062] Example 3: In this example, 20 ml of 0.2M Ca(NO3)2 solution and 40 ml of 0.4M Na2CO3 solution were added. It was calculated that the amount of calcium carbonate generated was 0.04 mol, which was 16 times that in Example 1. Under this condition, a large amount of calcium carbonate may be deposited on the surface of titanium dioxide.
[0063] 2. Analysis of photocatalytic effect
[0064] according to Figure 2 From the degradation rate data, the following trends can be observed:
[0065] The degradation rate of the control group was 15%, which is the photocatalytic effect of the pure titanium dioxide sample without calcium carbonate deposition. The degradation rate of Example 1 was 27%, which was significantly improved over the control group, indicating that an appropriate amount of calcium carbonate deposition can improve the photocatalytic effect of titanium dioxide. The degradation rate of Example 2 was 45%, which was further improved, indicating that more calcium carbonate deposition brought about a better photocatalytic effect. However, the degradation rate of Example 3 was 46%, which was still higher than the control group, but only increased by 1% compared to Example 2, indicating that the improvement in the photocatalytic effect was no longer significant.
[0066] Conclusion
[0067] Combined with the above analysis, it can be inferred that: when the amount of calcium carbonate deposited increases within a certain range (such as from Example 1 to Example 2), it can effectively improve the photocatalytic effect of titanium dioxide. However, when the amount of calcium carbonate deposited continues to increase to a certain extent (such as Example 3), too much calcium carbonate may cover the active sites on the surface of titanium dioxide, or hinder the separation and migration of photogenerated electrons and holes, resulting in the improvement of the photocatalytic effect is no longer significant, and may even show a downward trend. Therefore, when preparing a TiO3 / calcium carbonate composite structure, it is necessary to reasonably control the amount of calcium carbonate deposited to obtain the best photocatalytic performance.
[0068] In summary, the photocatalytic activity of the prepared titanium dioxide-calcium carbonate composite structure can be evaluated by the methylene blue degradation experiment. The experimental results show that the titanium dioxide-calcium carbonate composite structure has a significantly better photocatalytic effect than titanium dioxide, and its photocatalytic performance can be optimized by adjusting the deposition amount of calcium carbonate. This study provides strong support for the application of titanium dioxide-calcium carbonate composite structures in the fields of photocatalysis and environmental protection.
[0069] The above implementation modes are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering and technical personnel in the field shall fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material, characterized in that: include Step 1: Grind and clean the surface of the pure titanium sample to remove the oil and oxide layer on the surface, and dry it for later use; Step 2: using the pure titanium sample treated in step 1 as the anode of the micro-arc oxidation reaction and the stainless steel electrolytic cell as the cathode, adding electrolyte into the stainless steel electrolytic cell to perform micro-arc oxidation reaction and prepare a porous titanium dioxide structure; Step 3: Clean the porous titanium dioxide structure, dry it and set it aside; Step 4: The micro-arc oxidation sample treated in step 3 is placed in a mixed reaction solution of deionized water, Na2CO3 and Ca(NO3)2 and centrifuged for 10-20 minutes. After the reaction is completed, it is cleaned and dried to obtain a titanium dioxide-calcium carbonate composite structure.
2. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 1, characterized in that: In step 1, a pure titanium sample with a diameter of 10-20 mm and a thickness of 0.5-1 mm is polished step by step using 240#, 800#, and 1500# sandpapers, and then ultrasonically cleaned with ultrapure water for 5-10 minutes. After cleaning, it is dried at 80°C in a blast drying oven for 6-12 hours and then used for later use.
3. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 1, characterized in that: In step 2, the electrolyte adopts a phosphate system electrolyte or a silicate system electrolyte.
4. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 3, characterized in that: The phosphate system electrolyte is prepared by mixing disodium hydrogen phosphate, sodium hydroxide and disodium ethylenediaminetetraacetate in a ratio of 5-9:1-3:4-7.
5. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 3, characterized in that: The silicate system electrolyte is prepared by mixing calcium chloride, sodium silicate and disodium ethylenediaminetetraacetate in a ratio of 1:1:1 to 4.
6. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 5, characterized in that: In step 2, the micro-arc oxidation reaction adopts a constant voltage mode, with a voltage of 250-400V, a frequency of 20-60Hz, a duty cycle of 20%-60%, and a reaction time of 3-15min.
7. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 6, characterized in that: In step 3, the porous titanium dioxide structure is ultrasonicated with ultrapure water for 3 to 6 minutes, the ultrapure water is replaced and ultrasonicated for another 3 to 6 minutes, and this process is repeated 3 to 5 times to clean the surface. After drying at 80° C. in a forced air drying oven for 6 to 12 hours, the sample is placed in a drying dish for later use.
8. The method for preparing a titanium dioxide-calcium carbonate composite photocatalytic material according to claim 7, characterized in that: In step 4, the micro-arc oxidation sample treated in step 3 is placed in a centrifuge tube, and deionized water and a mixed solution of Ca(NO3)2 and Na2CO3 are added to the centrifuge tube, wherein the molar ratio of the mixed solution of Ca(NO3)2 and Na2CO3 is 1:2, and the centrifugal oscillation is performed for 10-20 minutes.